If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -17 + 2z = 10 Reorder the terms: -17 + 3z + 2z = 10 Combine like terms: 3z + 2z = 5z -17 + 5z = 10 Solving -17 + 5z = 10 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 5z = 10 + 17 Combine like terms: -17 + 17 = 0 0 + 5z = 10 + 17 5z = 10 + 17 Combine like terms: 10 + 17 = 27 5z = 27 Divide each side by '5'. z = 5.4 Simplifying z = 5.4
| 5(w-7)=9w-15 | | 10-(4-x)=30 | | (x+8)(x-122)=0 | | (4/z-3)-24/z^2-9)=1 | | 20x^9-25x^7+15x^5-40x^4=0 | | -8x^2-20x+x^4=0 | | (14*x^7-18*x^3)/(2x^3) | | X+y=320 | | x^2+8x-122=0 | | 225=10(x-60)+75 | | 10x+21=15-21 | | (x^2)+(4x)+4=49 | | uy=-2/3x-2 | | 12x^2+7x+6=0 | | y=-30x+900 | | -8x^2-33+x^4=0 | | .52+.18s=3 | | 2x=6(x+5)-4 | | A/11=24/8 | | (y-3)/(y-2) | | 8(x+4)+7=10x-2(x-6) | | .52+.185=3 | | 6r-17=1+9r | | 5.32/1.4= | | y-3/y-2 | | (2x+6)+(3x+4)=90 | | -(x^2+x-2)= | | 8+4(4x-6)=5-4(2x+1) | | 5x^2-12x-65=0 | | 14*0.3= | | 2/3a^2b-1/6ab | | (2x-6)+(3x+4)=90 |